Corporate social responsibility and job seekers' application intention: a mediated moderation model of calling and value congruence. Issue 1 (15th December 2020) - Choi, Jinsoo; Park, Yonguk; Sohn, Young Woo
Abstract : Purpose: This study investigated how and when corporate social responsibility (CSR) fosters job seekers' application intention using a mediated moderation model. Specifically, the study explored the positive effect of CSR on job seekers' intention to apply, the moderating role of applicants' calling and the mediating role of value congruence in the relationship between the person and organization. Design/methodology/approach: The study sample consisted of 259 college students in South Korea. A quasi-experimental design and survey were used. Data were analyzed using a regression-based path analysis to test a mediated moderation model. Findings: The results showed that CSR significantly increased job seekers' application intention, which was moderated by their calling. Furthermore, the interaction between CSR and calling on application intention was fully mediated by the value congruence between person and organization. Practical implications: The results suggest that engaging in active CSR can effectively attract job applicants, especially those with a high calling, who are known as qualified workers needed for the organization. The findings can provide a competitive advantage to organizations in this highly competitive environment. Originality/value: This study contributes to the understanding of the micro-effect of CSR by showing the positive influence of CSR on job seekers' application intention. Further, by evaluating a mediated moderation model, this study advances the field's understanding of the underlying mechanisms of CSR, especially in terms of calling and value congruence.